Fiber deviation and optimized toolpath strategies in melt electrowriting of tubular scaffolds - Benno Neuhaus; Sebastian Loewner; Henrik Heymann; Fritz Webering; Judith Synofzik; Holger Blume; Cornelia Blume (Materials & Design)
Melt electrowriting (MEW) onto a rotating cylindrical mandrel enables the fabrication of tubular scaffolds for tissue engineering, such as vascular grafts, with microstructures that support cellular ingrowth and customizable biomechanical properties. However, these scaffolds exhibit a systematic deviation of deposited fibers from the planned design, previously unreported in the existing literature. Unlike the known deviations in planar scaffolds, this deviation affects a wider range of designs, including meandering toolpaths, where it can result in pronounced alternating fiber spacing. Since this deviation often exceeds 100 µm and most biologically relevant structures are significantly smaller, it can compromise scaffold integrity, rendering the product unsuitable for clinical use.This study investigates the origin of this deviation using a novel automated optical scanning system consisting of a custom microscope integrated into a four-axis bioprinter. High-resolution images of entire tubular scaffolds are captured to precisely measure fiber deviation. Besides this empirical approach, a mathematical model was developed based on simple geometric considerations to predict deviation from jet and printing parameters, which closely matches experimental measurements. Finally, four toolpath strategies that avoid the alternating fiber spacing were evaluated. Some strategies reduce mean fiber spacing variation to ± 4 µm, facilitating the fabrication of highly homogeneous porous structures.